Continental Drivers of Population‐Level Intraspecific Trait Variability in Salamanders, Birds, and Small Mammals - Isadora E. Fluck; Sydne Record; Angela Strecker; Phoebe L. Zarnetske; Dean C. Adams; Morgan W. Tingley; Rodney B. Siegel; Benjamin Baiser (Global Ecology and Biogeography, 2026)
Aim Intraspecific trait variability (ITV) is a key component of biodiversity because it informs how organisms respond to abiotic and biotic conditions. Understanding how the variability among individuals within a population (population‐level ITV) changes along environmental gradients offers insight into how local processes contribute to broad‐scale biodiversity patterns. Here, we examine how climate and species‐richness interact to drive population‐level ITV across taxa with distinct life‐histories. Location United States and Canada. Time Period Present. Major Taxa Studied Plethodon salamanders, birds, and small mammals. Methods Individual body‐size measurements were compiled from multiple large‐scale biodiversity data sources, and population‐level ITV across populations of the focal taxa was quantified as the coefficient of variation (CV). Using Bayesian phylogenetic generalized linear mixed models (PGLMMs), we tested the effects of mean annual temperature, precipitation, and relative humidity, as well as their interactions with species richness, while accounting for species identity, phylogeny, and site. Results The influence of environmental predictors on population‐level ITV differed across taxonomic groups. Salamander ITV declined with humidity and increased with temperature in species‐rich sites, bird ITV increased with temperature, and small‐mammal ITV decreased with precipitation but increased with humidity and temperature in species‐rich sites. Main Conclusions We found that abiotic and biotic conditions shape trait diversity within populations, and that these factors differ across taxonomic groups according to their life‐histories. Groups with relatively low mobility and that are closely tied to their microhabitats showed increased population‐level ITV in warm, species‐rich environments. These findings challenge the classic niche‐packing expectations by suggesting that responses to climatic stress and interspecific competition can increase individual variation within populations, potentially reflecting differences in the strategies individuals adopt to cope with environmental challenges. Together, these insights underscore the importance of studying intraspecific trait variation for understanding macroecological patterns in biodiversity.

Here, There and Everywhere: Widespread Non‐Native Plants in the World's Urban Ecosystems - David M. Richardson; Lauren B. Trotta; Myla F. J. Aronson; Benjamin Baiser; Marc W. Cadotte; Marta Carboni; Laura Celesti‐Grapow; Sonja Knapp; Ingolf Kühn; Ana Carolina Lacerda de Matos; Zdeňka Lososová; Daijiang Li; et al. (Global Ecology and Biogeography, 2025)
Aim To (a) produce a list of the most widespread naturalised non‐native plant species across cities of the world; (b) explore whether cities on different continents are invaded by the same group of widespread naturalised species; and (c) elucidate the origins of the most widespread naturalised urban species. Location Global. Time Period No specific period. Major Taxa Studied Vascular plants. Method Using the most comprehensive and up‐to‐date dataset of non‐native urban floras yet assembled (GUBIC; Global Urban Biological Invasions Compendium), we identified the most widespread naturalised plant species (the global urban florome) by filtering for taxa present across all continents (except Antarctica) and their frequency in urban areas. To assess global patterns of urban plant naturalisation, we conducted ordination analyses and visualised species co‐occurrence. We also examined species origins and their environmental impact. Results Among the 7792 naturalised plant species recorded in 553 urban centres, 302 species (4%) were found on all six continents. Of these, 96 species, considered the most widespread species, were present in more than half of urban centres in Oceania, North America and South America; this proportion was higher than in Africa, Asia and Europe. Cities outside Europe and Asia are more homogeneous in terms of the species composition of the most widespread invaders. An analysis of species origins showed that temperate Asia contributed the most species globally, while intercontinental exchange patterns varied, with a notable one‐directional flow from North to South America. Main Conclusions Our results suggest that urban ecosystems outside Europe and Asia are more susceptible to recent invasions than those within these two continents. Understanding the composition and origins of these widespread species is crucial for developing coordinated management strategies and improving the resilience of urban biodiversity.

Top‐Down Processes Drive Taxonomic and Phylogenetic Diversity in a Model Aquatic Microbial Community - Alicia McGrew; Zachary B. Freedman; Benjamin Baiser (Ecology, 2025)
While the relative importance of bottom‐up and top‐down processes in structuring patterns of aquatic taxonomic diversity has been widely explored for many taxa, the response of aquatic microbial communities to bottom‐up: top‐down processes is not well understood. Further, studies of bottom‐up: top‐down processes in aquatic systems often focus on taxonomic diversity, leaving the response of other components of diversity (e.g., phylogenetic diversity) less clear. We used the model aquatic food web found in leaves of the pitcher plant Sarracenia purpurea to explore the influence of bottom‐up: top‐down processes on patterns of bacterial taxonomic and phylogenetic α‐ and β‐diversity. To explore the status of Wyeomyia smithii mosquito larvae as a prospective keystone predator of bacteria in this system, we developed two experiments where we manipulated resource level and the abundance of the top predator, W. smithii , in the presence or absence of intermediate consumers. Bacterial communities were assessed by high‐throughput sequencing of bacterial 16S rRNA genes and were interrogated using multiple components of taxonomic and phylogenetic α‐ and β‐diversity. Taxonomic α‐diversity decreased in the presence of mosquito larvae predators but was unaffected by predator number or resource level. Phylogenetic α‐diversity responses to bottom‐up and top‐down processes depended on the metric. Taxonomic and phylogenetic β‐diversity increased largely as a result of mosquito larvae predation; however, there was some influence of resource level, as well as differences in dispersion among levels of predation. We show that W. smithii mosquito larvae exerted strong top‐down control over taxonomic α‐ and β‐diversity in S. purpurea bacterial communities but did not act as a keystone predator. Predation by these larvae altered phylogenetic diversity through the removal of less abundant phylogenetic lineages, shaping both α‐ and β‐diversity. These experiments clarify the role of W. smithii in the S. purpurea model food web, provide novel insights into the response of bacterial communities to both bottom‐up and top‐down processes, and highlight the importance of using multiple components of diversity in bottom‐up: top‐down studies.

Dispersal Limitation Governs Bacterial Community Assembly in the Northern Pitcher Plant ( Sarracenia purpurea ) at the Continental Scale - Grace A. Cagle; Alicia McGrew; Benjamin Baiser; Sydne Record; Nicholas J. Gotelli; Dominique Gravel; Leonora S. Bittleston; Erica B. Young; Sarah M. Gray; Zachary B. Freedman (Global Ecology and Biogeography, 2024)
Aim Ecological theory suggests that dispersal limitation and selection by climatic factors influence bacterial community assembly at a continental scale, yet the conditions governing the relative importance of each process remains unclear. The carnivorous pitcher plant Sarracenia purpurea provides a model aquatic microecosystem to assess bacterial communities across the host plant's north–south range in North America. This study determined the relative influences of dispersal limitation and environmental selection on the assembly of bacterial communities inhabiting S. purpurea pitchers at the continental scale. Location Eastern United States and Canada. Time Period 2016. Major Taxa Studied Bacteria inhabiting S. purpurea pitchers. Methods Pitcher morphology, fluid, inquilines and prey were measured, and pitcher fluid underwent DNA sequencing for bacterial community analysis. Null modelling of β‐diversity provided estimates for the contributions of selection and dispersal limitation to community assembly, complemented by an examination of spatial clustering of individuals. Phylogenetic and ecological associations of co‐occurrence network module bacteria was determined by assessing the phylogenetic diversity and habitat preferences of member taxa. Results Dispersal limitation was evident from between‐site variation and spatial aggregation of individual bacterial taxa in the S. purpurea pitcher system. Selection pressure was weak across the geographic range, yet network module analysis indicated environmental selection within subgroups. A group of aquatic bacteria held traits under selection in warmer, wetter climates, and midge abundance was associated with selection for traits held by a group of saprotrophs. Processes that increased pitcher fluid volume weakened selection in one module, possibly by supporting greater bacterial dispersal. Conclusion Dispersal limitation governed bacterial community assembly in S. purpurea pitchers at a continental scale (74% of between‐site comparisons) and was significantly greater than selection across the range. Network modules showed evidence for selection, demonstrating that multiple processes acted concurrently in bacterial community assembly at the continental scale.

An analysis of long-term Everglades Stormwater Treatment Areas performance using structural equation models - Jing Hu; Benjamin Baiser; R. Thomas James; K. Ramesh Reddy (Ecological Engineering, 2024)

A global analysis of avian island diversity–area relationships in the Anthropocene - Thomas J. Matthews; Joseph P. Wayman; Robert J. Whittaker; Pedro Cardoso; Julian P. Hume; Ferran Sayol; Konstantinos Proios; Thomas E. Martin; Benjamin Baiser; Paulo A. V. Borges; Yasuhiro Kubota; Luiz dos Anjos; et al. (Ecology Letters, 2023)
Research on island species–area relationships (ISAR) has expanded to incorporate functional (IFDAR) and phylogenetic (IPDAR) diversity. However, relative to the ISAR, we know little about IFDARs and IPDARs, and lack synthetic global analyses of variation in form of these three categories of island diversity–area relationship (IDAR). Here, we undertake the first comparative evaluation of IDARs at the global scale using 51 avian archipelagic data sets representing true and habitat islands. Using null models, we explore how richness‐corrected functional and phylogenetic diversity scale with island area. We also provide the largest global assessment of the impacts of species introductions and extinctions on the IDAR. Results show that increasing richness with area is the primary driver of the (non‐richness corrected) IPDAR and IFDAR for many data sets. However, for several archipelagos, richness‐corrected functional and phylogenetic diversity changes linearly with island area, suggesting that the dominant community assembly processes shift along the island area gradient. We also find that archipelagos with the steepest ISARs exhibit the biggest differences in slope between IDARs, indicating increased functional and phylogenetic redundancy on larger islands in these archipelagos. In several cases introduced species seem to have ‘re‐calibrated’ the IDARs such that they resemble the historic period prior to recent extinctions.

Global patterns and drivers of raptor phylogenetic and functional diversity - Flavia Montaño‐Centellas; Benjamin Baiser; Alicia McGrew; Lauren Trotta; Daijiang Li (Global Ecology and Biogeography, 2023)
Aim Raptors, a highly threatened but ecologically important group of birds, have been recognized as a good proxy for overall biodiversity in conservation planning. However, previous work on raptor diversity focused predominantly on taxonomic diversity. Here, we assess the global patterns of raptor taxonomic, phylogenetic and functional diversity and their association with current and historical environmental factors. Location Global. Time period Present day. Major taxa studied Raptors. Methods We compiled information from distribution maps, global trait datasets and avian phylogenies for all extant raptors. We used generalized least squares (GLS) to assess the relationship between historical and contemporary environmental predictors and species richness, phylogenetic diversity [Faith's phylogenetic diversity index (Faith's PD), mean pairwise distance (MPD) and mean nearest taxon distance (MNTD)] and functional diversity of traits related to raptor morphology, lifestyles, diet, foraging and vagility, while controlling for spatial autocorrelation. Results Raptor taxonomic diversity peaked in tropical regions and nearby mountain ranges. After controlling for species richness, species‐poor assemblages in high latitudes and deserts were more phylogenetically and functionally diverse than expected by chance. In species‐rich assemblages, diet and foraging traits had greater variation, whereas morphological traits had less variation than expected, suggesting that species packing promoted adaptive radiation in these assemblages. Historical climate influenced phylogenetic diversity and functional diversity of morphological, foraging and diet traits, leaving a signal of evolutionary history on modern assemblages. Human footprint was also an important driver of MPD and of niche and vagility trait functional diversity, with higher phylogenetic diversity in disturbed areas and with higher functional diversity in regions with intermediate levels of disturbance. Main conclusions Both palaeoclimate and contemporary environmental conditions are important drivers of raptor phylogenetic and functional diversity. We found large mismatches among taxonomic, functional and phylogenetic diversity, demonstrating how different processes filter lineages and species traits shaping raptor assemblages. Our results highlight the need to consider multiple dimensions of diversity to inform conservation planning better when using raptors as umbrella species.

Functional and phylogenetic diversity of sharks in the Northeastern Pacific - Zachary A. Siders; Lauren B. Trotta; Fabio P. Caltabellotta; Katherine B. Loesser; Benjamin Baiser; Robert N. M. Ahrens (Journal of Biogeography, 2022)
Aim The expansive spatial scale of pelagic communities and the difficulty in acquiring pelagic species' functional traits have stymied an understanding of marine community dynamics. We assembled and analysed a shark trait database and community phylogeny to identify the major axes of trait variation that define shark functional groups. We tested whether membership to biophysical macroecological strata is related to these functional or phylogenetic relationships. Location Northeastern Pacific, 180–255°E and 0–50°N. Taxon Sharks (Class: Chondrichthyes, superorder: Selachimorpha). Methods We built a community phylogeny and collected habitat, reproductive, somatic growth, trophic and dentition traits. We used principal coordinates analyses to identify axes of trait variation and hierarchical clustering to classify functional groups. We tested whether functional or phylogenetic relatedness determined species' membership to strata from five macroecological gradients: latitude, habitat type, thermal, carbon source and bathymetry. Results We assembled 38 traits from 1225 records from 130 sources, 260 pictographs from seven sources and 631 teeth from 79 jaw specimens. Life history, r versus K selection, was responsible for the biggest division in the functional dendrogram. Vertical habitat preference, growth rates, diet and dental morphology generated further divisions between r ‐ or K ‐selected species. Vertical habitat preference, carbon source and biochemical habitat type were significantly dispersed or clustered on the functional dendrogram or phylogram. Main Conclusions Habitat and reproductive traits were the most important trait suites driving shark functional diversity. Through ordination and clustering, we were able to associate major axes of trait variation to the membership of shark functional groups. The phylogram approximated well the functional dendrogram's backbone but was a poor substitute for the trait diversity at the tips. Given the long evolutionary history of sharks and coincident expansive trait diversity, merging functional and phylogenetic approaches was necessary to capture the dimensions of shark biodiversity.

Urbanization delays plant leaf senescence and extends growing season length in cold but not in warm areas of the Northern Hemisphere - Daijiang Li; Brian J. Stucky; Benjamin Baiser; Robert Guralnick (Global Ecology and Biogeography, 2022)
Aim Urbanization is becoming one of the most important drivers of global environmental change as human population and economic development rapidly increase. However, the effects of urbanization on plant phenology are still poorly understood, especially for leaf senescence and growing season length across large spatial scales. We aimed to fill this knowledge gap by combining in situ observations and remote sensing phenological data. Location The United States and Europe. Time period 2009–2018. Major taxa studied Vascular plants. Methods We divided the United States and Europe into 10 km by 10 km grid cells. We estimated leaf senescence dates for 93 species, and growing season length for a subset of 54 of these species, for grid cells with enough data using a database with >22 million in situ phenology observations. We also estimated growing season lengths at the community level for the Eastern Temperate Forest ecoregion in the US using remote sensing data. We then investigated effects of urbanization (using human population density as a proxy), temperature, and their interactions on leaf senescence and growing season lengths using linear mixed models. Results Urbanization and warmer regional temperature both delayed plant leaf senescence. In addition, the effects of urbanization on leaf senescence and growing season lengths depended on climate context: urbanization delayed leaf senescence and extended growing season length in cold regions; however, urbanization advanced leaf senescence and shortened growing season length in warm regions, implying the positive effects of urbanization on growing season length in cold regions may be weaker in a warmer future. Main conclusions Our study provides strong empirical evidence that the influence of urbanization on plant phenology and growing season length varies with regional temperature. Our results have important implications for predicting plant phenology and growing season length in a warmer and more urbanized future.

Environment–host–microbial interactions shape the Sarracenia purpurea microbiome at the continental scale - Zachary B. Freedman; Alicia McGrew; Benjamin Baiser; Mathilde Besson; Dominique Gravel; Timothée Poisot; Sydne Record; Lauren B. Trotta; Nicholas J. Gotelli (Ecology, 2021)
The importance of climate, habitat structure, and higher trophic levels on microbial diversity is only beginning to be understood. Here, we examined the influence of climate variables, plant morphology, and the abundance of aquatic invertebrates on the microbial biodiversity of the northern pitcher plant Sarracenia purpurea . The plant's cup‐shaped leaves fill with rainwater and support a miniature, yet full‐fledged, ecosystem with a diverse microbiome that decomposes captured prey and a small network of shredding and filter‐feeding aquatic invertebrates that feed on microbes. We characterized pitcher microbiomes of 108 plants sampled at 36 sites from Florida to Quebec. Structural equation models revealed that annual precipitation and temperature, plant size, and midge abundance had direct effects on microbiome taxonomic and phylogenetic diversity. Climate variables also exerted indirect effects through plant size and midge abundance. Further, spatial structure and climate influenced taxonomic composition, but not phylogenetic composition. Our results suggest that direct effects of midge abundance and climate and indirect effects of climate through its effect on plant‐associated factors lead to greater richness of microbial phylotypes in warmer, wetter sites.

Ecogeographical rules and the macroecology of food webs - Benjamin Baiser; Dominique Gravel; Alyssa R. Cirtwill; Jennifer A. Dunne; Ashkaan K. Fahimipour; Luis J. Gilarranz; Joshua A. Grochow; Daijiang Li; Neo D. Martinez; Alicia McGrew; Timothée Poisot; Tamara N. Romanuk; et al. (Global Ecology and Biogeography, 2019)
Aim How do factors such as space, time, climate and other ecological drivers influence food web structure and dynamics? Collections of well‐studied food webs and replicate food webs from the same system that span biogeographical and ecological gradients now enable detailed, quantitative investigation of such questions and help integrate food web ecology and macroecology. Here, we integrate macroecology and food web ecology by focusing on how ecogeographical rules [the latitudinal diversity gradient (LDG), Bergmann's rule, the island rule and Rapoport's rule] are associated with the architecture of food webs. Location Global. Time period Current. Major taxa studied All taxa. Methods We discuss the implications of each ecogeographical rule for food webs, present predictions for how food web structure will vary with each rule, assess empirical support where available, and discuss how food webs may influence ecogeographical rules. Finally, we recommend systems and approaches for further advancing this research agenda. Results We derived testable predictions for some ecogeographical rules (e.g. LDG, Rapoport's rule), while for others (e.g., Bergmann's and island rules) it is less clear how we would expect food webs to change over macroecological scales. Based on the LDG, we found weak support for both positive and negative relationships between food chain length and latitude and for increased generality and linkage density at higher latitudes. Based on Rapoport's rule, we found support for the prediction that species turnover in food webs is inversely related to latitude. Main conclusions The macroecology of food webs goes beyond traditional approaches to biodiversity at macroecological scales by focusing on trophic interactions among species. The collection of food web data for different types of ecosystems across biogeographical gradients is key to advance this research agenda. Further, considering food web interactions as a selection pressure that drives or disrupts ecogeographical rules has the potential to address both mechanisms of and deviations from these macroecological relationships. For these reasons, further integration of macroecology and food webs will help ecologists better understand the assembly, maintenance and change of ecosystems across space and time.

For common community phylogenetic analyses, go ahead and use synthesis phylogenies - Daijiang Li; Lauren Trotta; Hannah E. Marx; Julie M. Allen; Miao Sun; Douglas E. Soltis; Pamela S. Soltis; Robert P. Guralnick; Benjamin Baiser (Ecology, 2019)
Should we build our own phylogenetic trees based on gene sequence data, or can we simply use available synthesis phylogenies? This is a fundamental question that any study involving a phylogenetic framework must face at the beginning of the project. Building a phylogeny from gene sequence data (purpose‐built phylogeny) requires more effort, expertise, and cost than subsetting an already available phylogeny (synthesis‐based phylogeny). However, we still lack a comparison of how these two approaches to building phylogenetic trees influence common community phylogenetic analyses such as comparing community phylogenetic diversity and estimating trait phylogenetic signal. Here, we generated three purpose‐built phylogenies and their corresponding synthesis‐based trees (two from Phylomatic and one from the Open Tree of Life, OTL ). We simulated 1,000 communities and 12,000 continuous traits along each purpose‐built phylogeny. We then compared the effects of different trees on estimates of phylogenetic diversity (alpha and beta) and phylogenetic signal (Pagel's λ and Blomberg's K). Synthesis‐based phylogenies generally yielded higher estimates of phylogenetic diversity when compared to purpose‐built phylogenies. However, resulting measures of phylogenetic diversity from both types of phylogenies were highly correlated (Spearman's > 0.8 in most cases). Mean pairwise distance (both alpha and beta) is the index that is most robust to the differences in tree construction that we tested. Measures of phylogenetic diversity based on the OTL showed the highest correlation with measures based on the purpose‐built phylogenies. Trait phylogenetic signal estimated with synthesis‐based phylogenies, especially from the OTL , was also highly correlated with estimates of Blomberg's K or close to Pagel's λ from purpose‐built phylogenies when traits were simulated under Brownian motion. For commonly employed community phylogenetic analyses, our results justify taking advantage of recently developed and continuously improving synthesis trees, especially the Open Tree of Life.

Comparing species–area relationships of native and exotic species - Benjamin Baiser; Daijiang Li (Biological Invasions, 2018)

Homogenization of species composition and species association networks are decoupled - Daijiang Li; Timothée Poisot; Donald M. Waller; Benjamin Baiser (Global Ecology and Biogeography, 2018)
Aim Ecological communities are composed of both species and the biotic relationships (interactions or spatial associations) among them. Biotic homogenization in species composition (i.e., increased site‐to‐site similarity) is recognized as a common consequence of global change, but less is known about how the similarity of species relationships changes over space and time. Does homogenization of species composition lead to homogenization of species relationships or are the dynamics of species relationships decoupled from changes in species composition? Location Wisconsin, USA. Time period 1950–2012. Major taxa studied Vascular plants. Methods We used long‐term resurvey data to analyse changes in plant species association patterns between the 1950s and 2000s at 266 sites distributed among three community types in Wisconsin, USA. We used species associations (quantified via local co‐occurrence patterns) to represent one type of relationship among species. Species pairs that co‐occur more or less than expected by chance have positive or negative associations, respectively. We then measured beta diversity in both species composition and species association networks over time and space. Results Shifts in species associations consistently exceeded the shifts observed in species composition. Less disturbed forests of northern Wisconsin have converged somewhat in species composition but little in species associations. In contrast, forests in central Wisconsin succeeding from pine barrens to closed‐canopy forests have strongly homogenized in both species composition and species associations. More fragmented forests in southern Wisconsin also tended to converge in species composition and in the species’ negative associations, but their positive associations diverged over the last half century. Species composition and associations are generally affected by a similar set of environmental variables. Their relative importance, however, has changed over time. Main conclusions Long‐term shifts in species relationships appear to be decoupled from shifts in species composition despite being affected by similar environmental variables.

The Interplay Between Landscape Structure and Biotic Interactions - Phoebe L. Zarnetske; Benjamin Baiser; Angela Strecker; Sydne Record; Jonathan Belmaker; Mao-Ning Tuanmu (Current Landscape Ecology Reports, 2017)

Decomposing biodiversity data using the Latent Dirichlet Allocation model, a probabilistic multivariate statistical method - Denis Valle; Benjamin Baiser; Christopher W. Woodall; Robin Chazdon (Ecology Letters, 2014)
We propose a novel multivariate method to analyse biodiversity data based on the Latent Dirichlet Allocation ( LDA ) model. LDA , a probabilistic model, reduces assemblages to sets of distinct component communities. It produces easily interpretable results, can represent abrupt and gradual changes in composition, accommodates missing data and allows for coherent estimates of uncertainty. We illustrate our method using tree data for the eastern United States and from a tropical successional chronosequence. The model is able to detect pervasive declines in the oak community in Minnesota and Indiana, potentially due to fire suppression, increased growing season precipitation and herbivory. The chronosequence analysis is able to delineate clear successional trends in species composition, while also revealing that site‐specific factors significantly impact these successional trajectories. The proposed method provides a means to decompose and track the dynamics of species assemblages along temporal and spatial gradients, including effects of global change and forest disturbances.

Geographic variation in network structure of a nearctic aquatic food web - Benjamin Baiser; Nicholas J. Gotelli; Hannah L. Buckley; Thomas E. Miller; Aaron M. Ellison (Global Ecology and Biogeography, 2012)
Aim The network structure of food webs plays an important role in the maintenance of diversity and ecosystem functioning in ecological communities. Previous research has found that ecosystem size, resource availability, assembly history and biotic interactions can potentially drive food web structure. However, the relative influence of climatic variables that drive broad‐scale biogeographic patterns of species richness and composition has not been explored for food web structure. In this study, we assess the influence of broad‐scale climatic variables in addition to known drivers of food web structure on replicate observations of a single aquatic food web, sampled from the leaves of the pitcher plant ( Sarracenia purpurea ), at different geographic sites across a broad latitudinal and climatic range. Location Using standardized sampling methods, we conducted an extensive ‘snapshot’ survey of 780 replicated aquatic food webs collected from the leaves of the pitcher plant S. purpurea at 39 sites from northern Florida to Newfoundland and westward to eastern British Columbia. Methods We examined correlations of 15 measures of food web structure at the pitcher and site scales with geographic variation in temperature and precipitation, concentrations of nutrients from atmospheric nitrogen deposition, resource availability, ecosystem size and the abundance of the pitcher plant mosquito ( Wyeomyia smithii ), a potential keystone species. Results At the scale of a single pitcher plant leaf, linkage density, species richness, measures of chain length and the proportion of omnivores in a web all increased with pitcher volume. Linkage density and species richness were greater at high‐latitude sites, which experience low mean temperatures and precipitation and high annual variation in both of these variables. At the site scale, variation in 8 of the 15 food web metrics decreased at higher latitudes, and variation in measures of chain length increased with the abundance of mosquitoes. Main conclusions Ecosystem size and climatic variables related to latitude were most strongly correlated with network structure of the Sarracenia food web. However, in spite of large sample sizes, thorough standardized sampling and the large geographic extent of the survey, even the best‐fitting models explained less than 40% of the variation in food web structure. In contrast to biogeographic patterns of species richness, food web structure was largely independent of broad‐scale climatic variables. The large proportion of unexplained variance in our analyses suggests that stochastic assembly may be an important determinant of local food web structure.

The relationship between functional and taxonomic homogenization - Benjamin Baiser; Julie L. Lockwood (Global Ecology and Biogeography, 2011)
Aim Species introductions and extinctions have reorganized the earth's biota, often leaving formerly spatially distinct assemblages more similar in species composition, a process termed biotic homogenization. The study of biotic homogenization has been almost entirely focused on the change in taxonomic similarity between assemblages through time. Here, we provide a trait‐based method for calculating functional similarity through time and compare these trends in functional attributes with those trends generated from a taxonomic perspective. Location Data were produced through computer simulation and gathered from North American Breeding Bird Survey (BBS) data and published accounts of North American birds for 10 locations across the east and west coast of the United States. Methods We simulated change in assemblages with different trait types (binary and continuous), levels of trait overlap, number of traits and species richness to determine the relationship between change in taxonomic similarity (ΔTS) and change in functional similarity (ΔFS). We also assess the relationship between ΔTS and ΔFS for bird assemblages across 10 locales in the USA between 1968 and 2008. We used simple linear regression to determine the slope and correlation between ΔTS and ΔFS and used multiple regression to assess the influence of trait overlap, number of traits, species richness and the ratio of traits to species on the relationship between ΔTS and ΔFS. Results Simulations reveal that trait redundancy governs the relationship between ΔTS and ΔFS. A decrease in trait overlap increases the slope of the regression between ΔTS and ΔFS and an increase in the ratio of traits to species in the regional pool increases the correlation. The relationship between ΔTS and ΔFS for breeding birds is comparable to simulations with low trait redundancy. Main conclusions We show that often losing or gaining species from an assemblage tells us very little about the loss or gain of function, and that this scenario most often occurs when the two assemblages have high trait redundancy. It remains to be seen how prevalent this scenario is within empirical examples; however, the implications for the continued delivery of ecosystem functions in the face of species introductions and extinctions are large.

A perfect storm: two ecosystem engineers interact to degrade deciduous forests of New Jersey - Benjamin Baiser; Julie L. Lockwood; David La Puma; Myla F. J. Aronson (Biological Invasions, 2008)